Phosphorylase and the origin of reversible protein phosphorylation - Fischer, Edmond (Henry Stewart Talks, 2010)
A historical account of the discovery of reversible protein phosphorylation, Video clips of the late Edwin Krebs speaking about our early work, Reversible protein phosphorylation represents one of the most prevalent mechanism by which cellular events are regulated, Establishment of the first hormonal cascade of successive enzymatic reactions initiated by cAMP